ACTIVE FRACTION OF BROWN SEAWEED Sargassum cinereum - Titieu Keumala Sukandar; Mery Sukmiwati; Andarini Diharmi (Berkala Perikanan Terubuk, 2021)
Sargassum cinereum brown seaweed contains phytochemical compounds such as alkaloids, flavonoids, steroids, saponins and phenolics, which are quite high. Different types of solvents can dissolve the bioactive components according to the polarity of the solvent used. Methanol solvent has a more effective level of polarity in dissolving all phytochemical compounds, one of which is flavonoids so as to produce the highest flavonoid compounds. Butanol extract only showed negative results in the flavonoid and saponin test. The hexane extract showed negative results only for the saponin test while the ethyl acetate extract showed positive results in all tests.